Information Policy of the Federal Reserve System and the European Central Bank During and After the Pandemic Crisis - Blicharski, Jakub (Journal of Finance and Financial Law, 2025)
The purpose of the article. Since the 1990s, central banks have become more transparent about their monetary policy. The meaning of the communication was amplified by the global financial crisis, when central banks began to use non-standard monetary policy instruments on a broader scale. Further changes resulted from the COVID-19 pandemic and the period of high inflation, which lasted several months afterwards. The article aims to present and analyse the measures taken by the Federal Reserve System (FED) and the European Central Bank (ECB) during the pandemic crisis and the period of high inflation. Methodology. The monetary policy instruments used by both central banks from 2020 to 2025, as well as the statements made by Jerome Powell (Chair of the Board of Governors of the FED) and Christine Lagarde (President of the ECB), were presented. The article also presents various opinions on the measures taken by both central banks, published in the press and the literature. Results of the research. The results indicate that monetary policy instruments, used by both central banks, allowed them to mitigate the effects of the economic disruptions caused by the COVID-19 pandemic. However, after the pandemic crisis, both central banks had to raise interest rates and pursue a policy of Quantitative Tightening. The crises also highlighted the importance of communication policy. Although the actions taken by both central banks were the subject of criticism, the measures taken by the FED were considered successful, and the measures taken by the ECB allowed for mitigating the direct consequences of the high inflation.